Aspects of Arbitral Awards in the Indonesian Justice System: Historical and Theoretical Review - Azwir Agus (Mahesa Research Center, 2023)
This study aims to analyze aspects of arbitral awards in the Indonesian justice system from historical and theoretical perspectives. The Arbitration Law confirms that arbitral awards have the same legal force as court decisions. The method used in this research is normative legal method. This legal method focuses on the analysis of existing legal norms, including statutory regulations, court decisions, legal principles, and other legal documents in this context, namely, aspects of arbitral awards in the Indonesian justice system. The results of the study show that the implementation of the arbitral award by the parties must be seen as a consequence of choosing arbitration to resolve the dispute, it is the parties who choose their own judges, even for their choice of law, then the implementation of the arbitral award is consciously a necessity of the parties themselves. Arbitration awards can be annulled in the justice system in Indonesia as a form of protection for justice and legal order. Grounds for annulment of an arbitral award, as provided for in the Arbitration Act, may include a breach of procedure, the incompetence of the arbitrator, or an award that violates decency or public decency. Arbitration awards are an important tool in the dispute resolution system in Indonesia, especially in the business and investment sphere.